Kedudukan Hukum Perjanjian Sewa Menyewa Tanah Seumur Hidup Oleh Warga Negara Indonesia Dengan Warga Negara Asing (Analisis Putusan Mahkamah Agung No. 112/Pdt.G/2016/PN Gin) - Prabandari, Ni Putu Dyah Ayu Karina; Santosa, Anak Agung Gede Duwira Hadi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024)DO - 10.24843/AC.2024.v09.i01.p1, 2024)
The aim of this article is to explore the issue concerning the legal status of incorporating a life clause within a leasehold agreement, taking into consideration the principle of good faith outlined in Article 1338 of the Civil Code and the legal implications regarding land in the Supreme Court decision No. 112/Pdt.G/2016/Pn Gin's verdict on a lease agreement case. According to the UUPA, the agreement is a temporary arrangement featuring a lawful cause clause, and there is no expectation of good faith that the property lease is meant to last a lifetime. This journal article employs normative legal research, incorporating legal, conceptual, and case-based methodologies, and is complemented by data collection through a mapping system. The findings of this study highlight the ongoing lack of legal certainty in the stipulations governing land leasing conditions, particularly within Article 1548 of the Civil Code. Furthermore, in accordance with the Supreme Court Judgment No. 112/Pdt.G/2016/Pn Gin, uncertainty persists regarding the land covered by the agreement, as governed by Article 21(1) UUPA, Article 26(2) UUPA, Article 1320 of the Civil Code, Article 1338 of the Civil Code, Article 1339 of the Civil Code, the principle of nationality, the principle of freedom of contract, and the principle of good faith. Ownership provisions also stipulate that properties in the nominee agreement must have expired or been released by the party controlling the property, subsequently leading to property forfeiture and state control.